2007
DOI: 10.1097/ppo.0b013e31813ffd7b
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Radiotherapy for the Treatment of Inoperable Non–Small Cell Lung Cancer

Abstract: Our data show a favorable 5-year overall survival rate (36%) with an acceptable toxicity profile in patients with early-stage NSCLC treated to doses of > or =80 Gy using three-dimensional conformal radiotherapy. Sequential chemotherapy combined with high-dose radiation gave survival rates equivalent to those seen with concurrent chemoradiation therapy in locally advanced disease. The overall survival and local control rates observed among patients with all stages of disease are consistent with and comparable t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 21 publications
1
23
0
2
Order By: Relevance
“…Unfortunately, outcomes for stage I patients who forgo treatment are dismal, with overall survival ranging from 9 to 14 months [7,22]. Outcomes of conventional EBRT appear to be better than with no treatment but are generally considered to be poor in comparison to either SBRT or surgery, with median overall survival ranging from 21 to 41 months and 5-year survival ranging from 15 to 39% [7,[23][24][25][26]. Our findings therefore suggest that Table 3 Factors associated with the use of SBRT when compared to less aggressive therapy (no treatment or EBRT) on multivariable analysis.…”
Section: Discussionmentioning
confidence: 98%
“…Unfortunately, outcomes for stage I patients who forgo treatment are dismal, with overall survival ranging from 9 to 14 months [7,22]. Outcomes of conventional EBRT appear to be better than with no treatment but are generally considered to be poor in comparison to either SBRT or surgery, with median overall survival ranging from 21 to 41 months and 5-year survival ranging from 15 to 39% [7,[23][24][25][26]. Our findings therefore suggest that Table 3 Factors associated with the use of SBRT when compared to less aggressive therapy (no treatment or EBRT) on multivariable analysis.…”
Section: Discussionmentioning
confidence: 98%
“…However, the target overall ventilation time in the NIPSV group was met after 3 days. Possible undesired negative effects such as alterations of hemodynamics, appearance of bronchopleural fistula or bronchial stump insufficiency have to be taken into consideration [13,14], as well as the limited or disputable benefit of surgical resection in expected high operative risk [32,33]. Particularly the group with reduced lung capacity bordering on inoperability was the target group of our investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Dose intensification can be accomplished by dose escalation (increasing the total radiation dose), acceleration (decreasing the overall treatment time), or a combination of the two. Studies of total dose escalation have demonstrated that when irradiation can be restricted to small volumes of lung tissue using 3DCRT, doses of up to 102.9 Gy could be delivered without excessive pulmonary toxicity [10,11]. Although a strong dose-response relationship was apparent, even at the highest dose levels of over 80 Gy, local failure in the irradiated field remained a significant problem with 5-year local control rates of 49% (including some locally advanced tumors) [10] to 67% [11].…”
Section: Conformal Radiotherapymentioning
confidence: 99%